Modern Method to Analyze the Heat Transfer in a Symmetric Metallic Beam with Hole - Șova, Daniela; Száva, Ildikó-Renáta; Jármai, Károly; Száva, Ioan; Vlase, Sorin (MDPI, Symmetry, 2022)
The paper aims to use Modern Dimensional Analysis to study the heat transmission through a rectangular bar with a hole. The problem is very important for monitoring a structure, made of such bars, to protect it from fire. The original part of the work is represented by the application of this nonconventional method in the field of heat transfer in bars of rectangular-tubular section. During system heating, the properties of the material change dramatically at high temperatures, which can lead to the collapse of the entire system. The Laws of the Model, further applied to the two sets of independent variables, provide the complete sets of dimensionless variables, which cannot be offered by any of the classical methods (such as Geometric Analogy, Theory of Similarity, and Classical Dimensional Analysis). The validation of the method was made experimental on both unprotected structural elements and those thermally protected with layers of intumescent paints, widely used in the field of fire protection. Finite Element Method was too applied to obtain the field of temperature in order to validate the model.
Keywords: Modern Dimensional Analysis; fire; rectangular beam; Model Law; monitoring